Hadith #5508 - Sahih al-Bukhari - Abdullah bin 'Amir عبد الله بن عامر بن يزيد بن تميم (Sahih al-Bukhari)
`Umar went to Sham and when he reached Sargh, he got the news that an epidemic (of plague) had broken out in Sham. `Abdur-Rahman bin `Auf told him that Allah’s Messenger (ﷺ) said, “If you hear that it (plague) has broken out in a land, do not go to it; but if it breaks out in a land where you are present, do not go out escaping from it.”
Grade: Sahih